VIOLENCE AND PAGANISM IN THE EARLY CAROLINGIAN FRANKISH WORLD: REPRESENTATIONS OF THE GERMANIC ALTERITY (8TH CENTURY) - Perl Garrido, Jonathan (Revista de Historia Social y de las Mentalidades, 2016)
The paper adressesone of the aspects on the issue of the construction of the representations of the otherness in the early Carolingian period. This otherness is considered to be identified with the people that were not included in the Frankish political unit nor in the Christian religious unit, established in the north-eastern regions of the Frankish kingdom of Austrasia, mainly Saxons and Frisians. In the definition of these people as “the Others”, religious and moral criteria played a fundamental role. From historiographical, hagiographical, epistolary and legal sources, a review is made on the wayin which the pagans were represented by the Christian authors, as characteristically violents towards Christendom (and the Frankish order), from which they are qualified inside the concept of “barbarians”. It is propossed and shown that the use of the resource to physical violence from the barbarians varies according to specific contexts in which the sources were produced, especially in terms of the contemporary development of the processes of evangelization and conquest of the forementioned regions, and those processes within the Frankish kingdom, related to the taking and maintenance of the power in the realm by the Carolingians